2022
DOI: 10.3390/sym14071312
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Buoyancy and Stagnation-Point Flow of Water Conveying Ag-MgO Hybrid Nanoparticles in a Vertical Contracting/Expanding Riga Wedge

Abstract: Riga surface can be utilized to reduce the pressure drag and the friction of the submarine by stopping the separation of the boundary layer as well as by moderating turbulence production. Therefore, the current symmetry of the work investigates the slip impacts on mixed convection flow containing water-based hybrid Ag-MgO nanoparticles over a vertical expanding/contracting Riga wedge. In this analysis, a flat surface, wedge, and stagnation point are also discussed. A Riga surface is an actuator that contains e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…They revealed that the addition of nanoparticles volumetric concentration diminished the blood velocity and temperature profiles. The discussions regarding the thermal and flow characteristics of hybrid nanofluids were reported by Khashi'ie et al [21][22][23][24] for disc case, Khan et al [25][26][27] for wedge and cylinder geometries and Lund et al [28][29][30][31] for stretching/shrinking plate. The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al [32][33][34][35][36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that the addition of nanoparticles volumetric concentration diminished the blood velocity and temperature profiles. The discussions regarding the thermal and flow characteristics of hybrid nanofluids were reported by Khashi'ie et al [21][22][23][24] for disc case, Khan et al [25][26][27] for wedge and cylinder geometries and Lund et al [28][29][30][31] for stretching/shrinking plate. The hybrid nanofluid flow subjected to the unsteadiness decelarating case was analyzed by Zainal et al [32][33][34][35][36] for various geometries.…”
Section: Introductionmentioning
confidence: 99%
“…[21–24] for disc case, Khan et al. [25–27] for wedge and cylinder geometries and Lund et al. [28–31] for stretching/shrinking plate.…”
Section: Introductionmentioning
confidence: 99%
“…Zeb et al [57] proposed the SBC on Non-Newtonian Ferrofluid over an extending slip. There are many studies [58][59][60] probed the problem of slippage velocity in the flow model. It had a prominent effect in clarifying this effect on the movement of the fluid and its temperature This looks at objectives to fill a familiarity hole withinside the flow and warmth transfer of a radiated Casson HNF with a variable thermal conductivity because the temperature rises, primarily based totally on the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Zeb et al 57 proposed the SBC on Non-Newtonian Ferrofluid over an extending slip. There are many studies [58][59][60] probed the problem of slippage velocity in the flow model. It had a prominent effect in clarifying this effect on the movement of the fluid and its temperature.…”
mentioning
confidence: 99%